Assessing dinner meals offered at home among preschoolers from low‐income families with the Remote Food Photography Method. Issue 11 (25th July 2019) - Bekelman, Traci A.; Bellows, Laura L.; McCloskey, Morgan L.; Martin, Corby K.; Johnson, Susan L.
Summary: Background: The high prevalence of obesity among preschoolers may be partially explained by the type and quantity of foods offered by parents and left unconsumed by preschoolers. Objectives: (a) To compare foods offered and consumed at dinner to the Dietary Guidelines for Americans (DGAs) and the Child and Adult Care Food Program (CACFP) standards and (b) to examine the types, quantities, and nutrient composition of foods offered to and consumed by preschoolers and their plate waste. Methods: Participants were recruited from six Head Start/preschool centres. The Remote Food Photography Method was used to document dinner meals over 1 week (n = 153 meals). Energy and nutrients for foods offered, consumed, and plate waste were calculated. Foods offered and consumed were compared with the DGAs and CACFP standards. Results: Foods and beverages offered at dinner equaled 506 kcal, which is 36% of the DGA‐recommended total daily energy intake. Meals offered and consumed were high in fat and sodium and low in fibre. Adherence to CACFP standards was low for fruits (25%) and milk (2%) and moderate for vegetables (63%). Mean plate waste (29%) was similar across food types. Conclusions: Opportunities exist to improve preschoolers' adherence to the DGAs and CACFP standards by enhancing the quality of dinner meals offered to them.